2022
DOI: 10.1093/jxb/erac497
|View full text |Cite
|
Sign up to set email alerts
|

Concentrating and sequestering biomolecules in condensates: impact on plant biology

Abstract: Growing examples of protein condensation phenomena prompt the re-evaluation of their functions in cells.We hereby discuss the possible implications of protein condensation for plant biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The authors employed an ATP biosensor fused to p33 or an LLPS‐deficient mutant to illustrate the crucial role of vir‐condensate formation in maintaining optimal local ATP production. Lin & Nagy's findings nicely complement previous literature that demonstrated that cellular condensates concentrate biomolecules and increase the efficiency of biochemical reactions (Mountourakis et al ., 2023). In summary, viral condensates may enhance virus fitness by facilitating the concentration of biomolecules, thereby improving the efficiency of energy‐intensive processes such as RNA replication.…”
Section: Figmentioning
confidence: 99%
“…The authors employed an ATP biosensor fused to p33 or an LLPS‐deficient mutant to illustrate the crucial role of vir‐condensate formation in maintaining optimal local ATP production. Lin & Nagy's findings nicely complement previous literature that demonstrated that cellular condensates concentrate biomolecules and increase the efficiency of biochemical reactions (Mountourakis et al ., 2023). In summary, viral condensates may enhance virus fitness by facilitating the concentration of biomolecules, thereby improving the efficiency of energy‐intensive processes such as RNA replication.…”
Section: Figmentioning
confidence: 99%
“…In the model plant, Arabidopsis (Arabidopsis thaliana) LLPS condensates are involved in, for example, the internal chloroplast cargo sorting, transcriptional circuits modulating defence, RNA processing, and temperature sensing [6][7][8][9][10]. Furthermore, plants form conserved condensates like stress granules and processing bodies [11][12][13]. Recent evidence suggests that like their animal counterparts, plant condensates can interface with membranes.…”
Section: Introductionmentioning
confidence: 99%
“…In the model plant, Arabidopsis (Arabidopsis thaliana) LLPS is involved in, for example, the internal chloroplast cargo sorting, defence, diurnal rhythms, RNA processing, and environmental sensing by forming plant-specific condensates [6][7][8][9][10]. Furthermore, plants form stress granules and processing bodies to sense and respond to environmental stimuli [11][12][13]. Condensates of the TPLATE, a plant-specific complex involved in endocytosis can likely form on the plasma membrane [14].…”
Section: Introductionmentioning
confidence: 99%